METHODICAL APPROACHES TO DESIGNING CABINET KITCHEN FURNITURE - ABYZOV, V. A.; KAMIONKA, L. W.; BULGAKOVA, T. V.; AHLIULLIN, R. M.; POLIAKOVA, O.V. (Art and Design, 2022)
The aim of this study is to identify the main approaches and develop methods for creating individual design of kitchen cabinet furniture. The kitchen with its furniture and equipment is an important part of the environment of residential buildings. Since equipping the kitchen with modern furniture, the latest materials and accessories also influences the formation of the artistic appearance of the interior, the study of the design of cabinet furniture in the living space is very important and timely at the present stage. Methodology. The study used the analysis of literature sources on the design of furniture; structural and system analysis; synthesis of research results; computer modelling. Results. Two main approaches to the design of kitchen cabinet furniture are identified: "from consumer to product" and "from product to consumer"; a method of creating individual design of kitchen furniture within the "from consumer to product" approach is developed; features of the "from product to consumer" approach are formulated. It is determined that the first approach is related to the individual design of furniture, in which certain wishes, requirements and ideas of the customer create the algorithm of work. These requirements can be dictated by the specifics of the interior of the room from aesthetic and functional points of view. The second approach is aimed at mass-produced kitchen furniture, which is more in line with large furniture production, where it is the manufacturer who selects the design, and the consumers adjust their desires to the offer of the company, which is more suitable for low-income consumers. Scientific novelty. For the first time, the basic approaches to the design of kitchen cabinet furniture are defined and characterized, and methods of creating individual design of kitchen cabinet furniture within the "from the consumer to the product" approach are developed. The practical significance of the obtained results lies in the possibility of their application for designers and manufacturers in the design of kitchen cabinet furniture.